The concept of enlightenment in the works of Farididdin Attor - Gulchehra Valerievna, Izbullaeva (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the educational views of Sheikh Fariduddin Attor, including categories of education, qualities, levels, virtues, methods of enlightenment, methods of education, the impact of education on human socialization, factors affecting education, paths, stages of knowledge formation, enlightenment features of being, spirituality, and unity of enlightenment.